2013
DOI: 10.1111/bpa.12055
|View full text |Cite
|
Sign up to set email alerts
|

24‐Year‐Old Woman with An Internal Auditory Canal Mass

Abstract: Benign peripheral nerve sheath tumors are divided into schwannomas, neurofibromas and perineuriomas. In recent years, tumors with hybrid features, composed of multiple, discrete areas of different histological types, were described. These tumors may represent a diagnostic challenge. A 24-year-old woman with multiple sclerosis was found to have a 1.3 cm TV × 0.7 cm AP T2 intermediate lesion within the left internal auditory canal. Gross examination revealed a tan-white, well circumscribed mass. Histologic exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 9 publications
3
6
0
Order By: Relevance
“…6,11,15,19 One tumor arising in the internal auditory canal showed almost identical features to our case 15, showing a biphasic pattern of schwannoma and perineurioma with formation of pseudoonion bulbs. 15 Three other tumors, one of which occurred in the mediastinum, were also composed of distinct schwannoma and perineurioma areas. 6,11,19 Interestingly, a spinal nerve tumor reported by Hayashi et al 14 showed complex microscopic features: schwannoma and perineurioma components were independently present among mixed cellular areas, suggesting the transitional form of mixed cellular and combined types of hybrid tumors.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…6,11,15,19 One tumor arising in the internal auditory canal showed almost identical features to our case 15, showing a biphasic pattern of schwannoma and perineurioma with formation of pseudoonion bulbs. 15 Three other tumors, one of which occurred in the mediastinum, were also composed of distinct schwannoma and perineurioma areas. 6,11,19 Interestingly, a spinal nerve tumor reported by Hayashi et al 14 showed complex microscopic features: schwannoma and perineurioma components were independently present among mixed cellular areas, suggesting the transitional form of mixed cellular and combined types of hybrid tumors.…”
Section: Discussionsupporting
confidence: 75%
“…5 Others including our case 15 had an intraneural perineurioma component and arose in other sites, such as the mediastinum. 11,15 Furthermore, our case 15 was associated with neurofibromatosis type 2, whereas the mixed cellular type lacks neurofibromatoses. 7,13 To avoid confusion in the nomenclature, this type of HSP could be renamed combined (or composite) schwannoma and perineurioma.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…The patient was a 36-year-old male with a black tumor on his arm since birth. Also in 2013, Las Heras et al [28] reported the first ever case of a hybrid perineurioma/schwannoma in a cranial nerve. The patient was a 24-year-old female with an internal auditory canal mass.…”
Section: Discussionmentioning
confidence: 99%
“…Typically, HNST consists of a painless mass in subcutaneous tissue or dermis [ 48 ]; when large peripheral nerves or spinal nerves are involved, the tumor may be associated with pain or neurological impairment. The most common site of HNST are the fingers [ 49 ], but some rare cases arise from cranial nerves [ 50 , 51 , 52 ]. Hybrid schwannomas/perineuriomas are sporadic [ 52 ], while hybrid neurofibroma/schwannomas are strongly associated with NF1 and 2, and schwannomatosis [ 53 ].…”
Section: Epidemiology and Clinical Featuresmentioning
confidence: 99%